Rheumatology and Rheumatoid Arthritis in the Twenty-First Century - Kay, Lesley J. (Seminars in Musculoskeletal Radiology, 2012)
Rheumatoid arthritis (RA) has historically been a disabling and life-threatening disease. Features include joint pain, stiffness and swelling, joint damage, fatigue, loss of function, and loss of employment. Recent advances in treatment, particularly the use of conventional disease-modifying therapies earlier and in combination, and the advent of biological therapies, ensures that modern rheumatologists expect to help patient attain remission, with advantages of early presentation and effective therapies used in a “treatment to target” strategy. Adherence to UK National Institute for Health and Clinical Excellence guidance for RA, including early identification of disease, early and aggressive use of disease-modifying antirheumatic therapies, in combination or with biological agents, allows for much better disease control and perhaps remission. Delays to diagnosis will therefore become increasingly important, and the necessity for accurate diagnosis becomes crucial. The strategy of tight disease control may be more important than the contribution of individual drugs, even biological agents. Future prospects include the use of better outcome measures to define remission, better prediction of outcome, and thus better targeting of therapies. There is an urgent need for better individualized prognostic predictors. We must not forget the management of patients with pain owing to damage from advanced disease. Rheumatologists and radiologists must work together to appreciate the opportunities for patients from a greater understanding of disease measurement.
Keywords: rheumatoid arthritis; inflammatory arthritis; remission; prognostic factors; treatment to target